Rehabilitation Interventions for Children With Cerebral Palsy: A Systematic Review - Ali Abbaskhanian; Vahid Rashedi; Ataollah Delpak; Roshanak Vameghi; Masoud Gharib (Mazandaran University of Medical Sciences, 2015)
Context: Cerebral palsy (CP) is a group of movement problems that do not worsen over time. They cause physical disability mainly in areas of body movement. It is caused by damage to the motor control centers of developing brain. Management of a child with CP to optimize functional abilities, typically includes the input of many disciplines, including occupational therapy (OT), physical therapy (PT) and orthotic treatment. The main aim of this review was to compare the effects of most common rehabilitation intervention on CP. Evidence Acquisition: This systematic review was conducted on published papers that studied rehabilitation interventions approaches for children with CP. A literature search was performed using PubMed, SCOPUS and Google Scholar on papers published from January 1990 to October 2014. Results: From 125 articles related to rehabilitation interventions for children with Cerebral palsy, 36 articles met the inclusion criteria. Conclusions: The efficacy of rehabilitation interventions for children with CP is still inconclusive. Functional ability and social participation should be the main outcome measures in evaluating rehabilitation efficacy.